The Measurement of Service Quality in Cianjur Raya Restaurant using SERVQUAL Model. - Stefani Angmalisang (AIBPM Publisher, 2018)
There is a significant need for the management in Cianjur Raya restaurant to do a service quality measurement, doe to the unsatisfied economic return and poor perform in meeting the desirable income level was set by the management.Hence, SERVQUAL model was being used in this research in order to measure the service quality in the restaurant. The model is useful to measure the gap between expectations of the customer with the fact of service that was delivered by the management. There are five SERVQUAL dimensions that represent the service quality; they are tangible, reliability, responsiveness, assurance and empathy. And the five dimensions are used to measure the five Gaps Analysis in SERVQUAL model which are: Gap 1 is the knowledge gap (the gap between customer expectations and perceptions of management); Gap 2 is the standards gap (the gap between management perceptions of consumer expectations and service quality standards); Gap 3 is the delivery gap (the gap between service quality specifications and delivery services); Gap 4 is the communication gap (the gap between service delivery and external communication); and Gap 5 is the service gap (the gap between perceived service and expected service). After conducting the research, the result found that the expected service was not met by the management; hence the service level was unsatisfactory. Finally, some recommendations were made to the management based on the result found in the research. The recommendation will be very useful in improving the service quality of Cianjur Raya restaurant in the near future. Keywords: Service Quality, SERVQUAL model, SERVQUAL dimensions, Gap.